Changes in the Effective Connectivity of the Social Brain When Making Inferences About Close Others vs. the Self - Esménio, Sofia; Soares, José Miguel; Oliveira-Silva, Patrícia; Gonçalves, Óscar F.; Friston, Karl; Fernandes Coutinho, Joana (Frontiers in Human Neuroscience, 2020)
Previous research showed that the ability to make inferences about our own and other’s mental states relies on common brain pathways; particularly in the case of close relationships (e.g., romantic relationships). Despite the evidence for shared neural representations of self and others, less is known about the distributed processing within these common neural networks, particularly whether there are specific patterns of internode communication when focusing on other versus self. This study aimed to characterize context-sensitive coupling among social brain regions involved in self and other understanding. Participants underwent an fMRI while watching emotional video vignettes of their romantic partner and elaborated on their partner´s (other-condition) or on their own experience (self-condition). We used dynamic causal modelling (DCM) to quantify the associated changes in effective connectivity in a network of brain regions involved in social cognition including the temporoparietal junction (TPJ), the posterior cingulate (PCC)/precuneus and middle temporal gyrus (MTG). DCM revealed that: the PCC plays a central coordination role within this network, the bilateral MTG receives driving inputs from other nodes suggesting that social information is first processed in language comprehension regions; the right TPJ evidenced a selective increase in its sensitivity when focusing on the other's experience, relative to focusing on oneself.